Polimorfismo do gene da interleucina IL-1B e sua associação com o risco ao desenvolvimento do câncer gástrico em uma população do norte do Brasil - CASTRO, Yaisa Gomes de (Universidade Federal do Pará, 2017)
Cancer is understood as a set of diseases with similar characteristics, but with great heterogeneity that occurs in a random manner and covers both tumor and inflammatory and immune cells. Gastric tumors, in Brazil and notably in the State of Pará, have a high incidence. In general, gastric cancer has a multifactorial etiology. Communication and cellular signaling that regulate the immune system are facilitated by interleukins that represent small, specific proteins, have diverse functions, they regulate transcription factors, role genes, inflammation, differentiation, proliferation, and secretion of antibodies. Single polymorphism nucleotide, in specific IL-1B proinflammatory interleukin gene, is associated with the immune response to H. pylori infection. Thefore variations within the IL-1 family genes were associated with susceptibility to the development of gastric cancer. In this case-control study, we investigated whether the polymorphisms IL-1BF1 (rs16944) and IL-1BE1 (rs1143627) are associated with the risk of developing gastric cancer in a population from the north of Brazil; Compared to their respective genotypes, defined haplotypes and these related to ancestry and their rates. SNPs were genotyped by VIC / FAM (Real Time PCR, Fluorescent, Life Technologies, CA, USA) labeled probes. The biostatistical analyzes showed that for the demographic variables, there were significant differences between the groups in European and African ancestry. The distribution of the genotypic, allelic and haplotype frequencies of the IL-1B gene was not statistically significant between the groups. More comprehensive studies and analyzes are needed to help understand better why these polymorphisms in this population do not appear to be associated with the development of the disease in question.